Complete Denture Prosthodontics Planning and Decision-Making (Springer International Publishing, 2018)
This excellently illustrated book equips dental students and practitioners with all the information and guidance required in order to plan optimally the treatment of edentulous patients. Introductory chapters identify the anatomic landmarks and age-related changes in these patients and explain how evaluation should be performed. Preprosthetic planning and impression procedures are then described in detail, covering key principles, mouth preparation, selection of impression material and technique, construction and adjustment of the custom tray, and border molding techniques. The final part of the volume focuses on establishing the occlusal relationship. Readers will find clear explanation of concepts of occlusion in prosthodontics, the recording of maxillomandibular relations, types of mandibular movement, and other important topics. Throughout the book, much attention is devoted to problem solving. A companion volume covering the implementation of complete denture treatment, including resolution of postinsertion problems, is available separately.